ALAT MONITORING DETAK JANTUNG PORTABLE MENGGUNAKAN SENSOR MAX30102 - Ramlan Bugis, Elmi Ramlan; Nur’Aidha, Amalia C.; Kumarajati, Dhananjaya Yama Hudha (Universitas Lampung, 2024)
Heart disease is a condition in which the heart cannot function properly and is one of the leading causes of death worldwide. This research aims to develop a device to identify the electrical activity generated by the heart, as the heart contracts by using electronic components to monitor and record a person's heartbeat. The tool to detect heart rate is made simple, lightweight and small that can be carried or moved easily. Tests were carried out by comparing measurements of tools made with Oximeter and showed an error rate of 6.41%. The average error based on the data obtained is 2.61%. By considering the disturbances that occur during measurement, it is certain that the monitoring tool made works well.